Intelligent system to provide precision of assembly processes in manufacturing and maintenance - Katargin, Vladimir N.; Pisarev, Ilya S. (Univerzita Pardubice, 2010)
The system suggested was developed to make the assembly processes in manufacturing and maintenance of aggregates more precise. The auxiliary surfaces, components, units and their couplings, that are in contact with replaceable or other component parts are taken into consideration. The system based on tracing the speed changes in wearing-out during the operation process, the couplings conditions produced by the parts in aggregate or units. The methods of decision-making when kitting-up the whole list of aggregate items for assembly from the view point of providing the necessary precision of the coupling parameters are employed. All geometrical parameters as they were given in the original aggregate design are restored. The correlation and interdependence of the dimensions of parts in aggregates or in the vehicle can be showed up with assembly dimension lines. At present a prototype of the program has been developed. It enables to realize the advantages of the suggested system in providing the precision of assembly processes in manufacturing and maintenance. On the basis of the method suggested it will be possible to create the on-line sources, which allow to make the system more flexible, universal and useful for enterprises and organizations dealing with complex aggregates maintenance.
Keywords: dimension analysis; assembly precision